Pelatihan Fasilitator Belajar Untuk Tingkat Sma Tahun Ajaran 2019 - Yubali Ani; Ashiong Parhehean Munthe; Widiastuti Widiastuti (Asosiasi Sinergi Pengabdi dan Pemberdaya Indonesia (ASPPI), 2019)
This activity is a continuation of the 2018-2019 FY training, with the training of high school students from class X and XI as a participant. All students involved were foster children from the Emmanuel Foundation. Compensation from scholarships, high school students are required to assist in learning to read and write for children of primary and early school age around their homes. The high school students certainly do not have the ability to teach, because they are not teachers. Therefore, the Emmanuel Foundation equips these high school students with training for learning facilitators. The purpose of this activity is that students are able to present a learning exhibition about: 1) the ability to spell and read; 2) basic mathematics; 3) making mind mapping; 4) telling stories through story books; 5) explain simple games; and 6) explain the procedure. This training activity was held on Saturday as many as eight meetings for one semester in the Sentul area. Saturday schedule for activities, at 09.00-15.00 and carried out in January-June 2019. The training activities went well, the students in the group were able to present each lesson that was made in accordance with the assessment rubric. Keywords: training, facilitator, learning, mind mapping, class procedures